Effect of extracellular Ca(2+) on the quinine-activated current of bullfrog taste receptor cells - Tsunenari, Takashi (Blackwell Science Inc, 2001)
1. The bitter substance quinine activates a cation current from the frog taste receptor cell. We have analysed the noise associated with this current, and the effect of extracellular Ca(2+) on the current, using whole-cell recording on single dissociated cells. 2. Quinine induced an inward current from the taste receptor cell near the resting potential. The response was accompanied by an increase in current fluctuations. From the variance/mean ratio of the quinine-activated current, the single-channel conductance was estimated to be 12 pS in the nominal absence of extracellular Ca(2+). In the presence of 1.8 mM Ca(2+), this conductance decreased to 5 pS. These values broadly agree with those previously obtained from excised, outside-out membrane patches. 3. The dependence of the current on quinine concentration had a K(1/2) of 0.48 mM in the absence of extracellular Ca(2+), consistent with measurements from excised patches. The K(1/2) value increased to 2.8 mM in 1.8 mM external Ca(2+). The maximum current induced by quinine was also reduced by about 20% by Ca(2+). 4. The spectral power density distribution of the quinine-activated current could be described by the sum of two Lorentzian functions, with corner frequencies not substantially different in the absence and presence of 1.8 mM external Ca(2+). 5. The above results lend further support to the notion that the major component of the response of frog taste receptor cells to quinine comes from an ion channel directly activated by quinine.